Allanblackia stuhlmannii – a tree under current domestication: what are the soil requirements? - Alvum-Toll, Kajsa (2013)
Allanblackia is a genus of trees that grows in the rainforests of West, Central and Eastern Africa. Its big fruits contain seeds very rich in oil which has been used by local communities for cooking and making soaps. The native stands are threatened by overexploitation and the demand for the oil is much greater than the supply.